Accuracy and Safety of AI-Enabled Scribe Technology: Instrument Validation Study - Joshua Biro; Jessica L Handley; Nathan K Cobb; Varsha Kottamasu; Jeffrey Collins; Seth Krevat; Raj M Ratwani (Journal of Medical Internet Research)
Artificial intelligence–enabled ambient digital scribes may have many potential benefits, yet results from our study indicate that there are errors that must be evaluated to mitigate safety risks.